Socio-Economic Analysis of Neighborhood Issues facing MPS Students and Their Families in Zipcode 53204 - (:unkn) unknown (My University, 2009)
As a planning supplement to the annual count of school children in the city of Milwaukee, the Employment and Training Institute assembled administrative and institutional data bases to help provide a socio-economic analysis of neighborhood issues facing Milwaukee Public Schools students and their families. Nine Milwaukee zip codes historically targeted for Community Development Block Grant funding because of their concentrations of poverty are analyzed in detail. This report provides neighborhood drilldowns on key issues of concern to educators for Milwaukee zip code 53204. The zip code drilldowns explore interrelationships at the neighborhood level between earnings of Milwaukee parents; job availability; the economic recession; expansion of the subsidized child care provider network; state welfare regulations; crime; incarceration and prisoner release rates; traffic dangers; and the housing foreclosure and eviction crises. These factors individually and in combination have profound impacts on the learning environment in the classroom.
Keywords: neighborhood indicators; community assets; crime; housing